2021
DOI: 10.1093/cercor/bhab068
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Excitatory and Inhibitory Neuronal Activity to BOLD fMRI

Abstract: The BOLD fMRI response in the cortex is often assumed to reflect changes in excitatory neural activity. However, the contribution of inhibitory neurons to BOLD fMRI is unclear. Here, the role of inhibitory and excitatory activity was examined using multimodal approaches: electrophysiological recording, 15.2 T fMRI, optical intrinsic signal imaging, and modeling. Inhibitory and excitatory neuronal activity in the somatosensory cortex were selectively modulated by 20-s optogenetic stimulation of VGAT-ChR2 and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…1 E ). Since inhibitory neural activation induces a hemodynamic response at the stimulation site ( 36 , 37 ) and in downstream regions, the contribution by this type of activation should be removed. It is assumed that the common photostimulation-driven hemodynamic response is completely eliminated by calculating the difference between the optogenetic fMRI responses observed with and without sensory stimulation (Comb − Opto = Diff in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 E ). Since inhibitory neural activation induces a hemodynamic response at the stimulation site ( 36 , 37 ) and in downstream regions, the contribution by this type of activation should be removed. It is assumed that the common photostimulation-driven hemodynamic response is completely eliminated by calculating the difference between the optogenetic fMRI responses observed with and without sensory stimulation (Comb − Opto = Diff in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although GABAergic interneuron activity is known to regulate local vascular tone by the release of vasoactive mediators (e.g., nitric oxide) ( 49 ), their activity also interacts with nearby excitatory neurons in the cortex. When inhibitory neurons were activated in VGAT-ChR2 mice, an increase in CBF and CBV was observed for <5 s of stimulation ( 37 , 50 , 51 ), indicating that inhibitory neurons indeed increase hemodynamic responses. However, the increased inhibitory activity by optogenetic stimulation suppressed excitatory activity (inhibition), which led to a decrease in hemodynamic responses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since MRI studies rely on Blood Oxygen Level Dependent (BOLD) signals as surrogates for neuronal activity (Hillman, 2014;Howarth et al, 2021;Moon et al, 2021), it is possible that changes in rCBF reflect changes in underlying neuronal activity. For instance, cerebral cortex hypoperfusion in ASD patients could reflect lower metabolic demands (Schifter et al, 1994).…”
Section: Altered Cerebral Blood Flow In Autism Spectrum Disordersmentioning
confidence: 99%
“…The physiological mechanisms underlying the task-induced negative BOLD phenomenon (deactivation) remain unclear [28], which is thought to be dependent on the stimulus type (task) and brain region [29]. However, numerous recent studies have suggested that this phenomenon may reflect neuronal inhibition [30][31][32][33][34][35][36][37][38] without exception in the central sensory-motor network [39,40].…”
Section: Negative Bold Phenomenonmentioning
confidence: 99%